Nitinol Staple versus Traditional Plate Osteosynthesis for Primary Arthrodesis of Lisfranc Injuries: A Retrospective Analysis. Issue 1 (February 2023) - Dombrowsky, Alexander R.; Strickland, Carson D.; Walsh, Devin F.; Conti, Matthew S.; Irwin, Todd A.; Cohen, Bruce E.; Ellington, J. Kent; Jones, Carroll P.; Shawen, Scott B.; Ford, Samuel E.
Category: Trauma; Midfoot/Forefoot Introduction/ Purpose: Primary arthrodesis of Lisfranc and midfoot fracture-dislocations is a reliable treatment option, yet concerns remain about nonunion and dorsiflexion malunion. The use of a new generation of nitinol staples has proliferated in midfoot arthrodesis. The purpose of this study is to examine the use of nitinol staples in primary arthrodesis of acute Lisfranc fracture-dislocations, comparing outcomes to traditional plate and screw fixation. The primary hypothesis is that nonunion rates are lower with constructs that include nitinol staples than those with plates and screws alone. Secondary hypotheses are: 1. Total operative and tourniquet time are shorter using nitinol staples. 2. Reoperation rates are lower using nitinol staples. 3. Dorsiflexion malunion rates are lower using nitinol staples. 4. Functional outcome scores will indicate comparable post-arthrodesis disability. Methods: Midfoot fracture-dislocations treated with primary arthrodesis by seven foot and ankle orthopaedic surgeons at a tertiary referral center from 1/1/2012 to 8/1/2021 were reviewed. Patients with open fractures, fractures managed with external fixation, Charcot arthropathy, neuropathy, previous midfoot surgery, or concomitant hindfoot/ankle fractures were excluded. Of 160 eligible patients, 121 patients met the required 4-month minimum radiographic follow-up. Preoperative records were reviewed, evaluating for associated metatarsal and cuneiform fractures, operative and tourniquet time, joints included, and fixation construct. Outcomes were analyzed at both patient and individual joint levels. Patients (121 total) and individual joints (305 total) were categorized as either staples alone (45 patients, 154 joints), staples plus plates and screws (hybrid) (45 patients, 40 joints), or plates and screws alone (31 patients, 111 joints). Postoperative radiographs were analyzed for union and malunion at each joint fused. Medical records were reviewed for postoperative complications. FAAM, VR-12, and NPRS were collected. Results: When assessed at the individual joint level, the nonunion rate was higher (8.1%, 9/111) among joints fixed with plate and screw constructs than with hybrid (2.5%, 1/40) or staple only constructs (1.3%, 2/154) (P = 0.017). Of the 12 nonunions in the study, 6 had either a metatarsal or cuneiform fracture. Median OR and tourniquet time were both shorter for hybrid (92 & 83 minutes) and staple only (67 & 63 minutes) constructs compared to plate and screw only fixation (106 & 95 minutes) (P = 0.0003 & < 0.0001). There were 15 (12.4%) reoperations including 10 hardware removals, 3 nonunion revisions, and 1 malunion revision. There was no difference in reoperation, malunion (14 total, 11.6%), or patient reported outcome measure between fixation types. Conclusion: Nitinol staples are effective in achieving bony fusion when used alone or in combination with plates and screws. Their use should be considered for primary arthrodesis of Lisfranc and midfoot fracture-dislocations due to lower rates of nonunion and shorter tourniquet and operative time compared to traditional plate and screw fixation. Further studies are needed to determine if staples decrease the risk for dorsiflexion malunion and improve patient reported outcomes.